The standardized letter of evaluation in emergency medicine: Are the qualifications useful?. Issue 3 (11th June 2021) - Miller, Danielle T.; Krzyzaniak, Sara; Mannix, Alexandra; Alvarez, Al'ai; Chan, Teresa; Davenport, Dayle; Eraso, Daniel; Foote, C. J.; Gore, Katarzyna; Parsons, Melissa; Gottlieb, Michael
ABSTRACT: Objectives: The standardized letter of evaluation (SLOE) in emergency medicine (EM) is a widely used metric for determining interview invitations and ranking of candidates. Previous research has questioned the validity of certain sections of the SLOE. However, there remains a paucity of literature on the qualifications for EM section, which evaluates seven attributes of applicants. The aim of this study was to determine the correlation between the qualifications questions and grades, global assessment, and anticipated rank list position for EM applicants. Methods: A multi‐institutional cross‐sectional study was performed using SLOEs from applicants to three geographically distinct U.S. EM residency programs during the 2019–2020 application cycle. We abstracted EM rotation grade, qualifications scores, global assessment, and anticipated rank list position from the SLOEs. A Spearman correlation was calculated between each of the qualifications scores and the applicant's grades, global assessment, and anticipated rank list position in a pairwise fashion. Results: In total, 2, 106 unique applicants (4, 939 SLOEs) were included. Of the seven qualifications for EM questions, three were moderately to strongly correlated with global assessment and anticipated rank list position: "ability to develop and justify an appropriate differential and a cohesive treatment plan" (ρ = 0.65 and ρ = 0.63, respectively; p < 0.001), "how much guidance do you predict this applicant will need during residency?" (ρ = 0.68 and ρ = 0.68, respectively; p < 0.001), and "what is your prediction of success for the applicant?" (ρ = 0.69 and ρ = 0.69, respectively; p < 0.001). There was no strong correlation between the seven qualifications and grades. Conclusions: There was a moderate to strong correlation between three of seven qualifications for EM questions (ability to develop and justify a differential and develop a cohesive plan, anticipated need for the amount of guidance, and prediction of success) with both global assessment and anticipated rank list position, suggesting that these qualifications may provide the most useful data to residency selection while some of the other factors may not be needed.